(untitled) (Al-Aasar, 2025)
The foundations of Islamic economics lie in the system of moral and ethical teaching presented in the Islamic faith and oriented to the concord of economic life with spiritual and social well-being of people and society. This study looks at the elementary Islam philosophy of economics and throws light on its distinctive principles in respect to the contemporary period. Unlike the classical economic systems whose major driving force is maximization of profits and materialistic gains, in Islamic economics moral aspects, social justice and equitable distribution of wealth are involved. Halal (permissible) and Haram (prohibited) are the key thoughts of this philosophy that provide severe guidelines of how legal economic practice has to be pursued. The boundary between Halal and Haram renders the economic exchange to be Shariah compliant and steers clear of the predatory economic dealings such as usury (Riba), gambling (Maisir) and insecurity (Gharar). This system promotes ethical investments, risk-sharing and circulation of wealth through the power of Zakat and Waqf among others that will minimise poverty and social cohesion. The changes within the financial system, the high pace of globalization, and technological innovations are the features of the modern world, which are regarded as the primary threats to and opportunities of the introduction of the Islamic economic principles. The research represents a critical reflection of how the major principles of the Islamic economics may be adapted to address the modern socio-economic issues like a sustainable development, financial inclusion and ethical finance. The research reinstates the relevance of the application of the Halal and Haram in the economic decision-making process and consequently, the Islamic economics can offer an alternative paradigm capturing the balance between material wealth and moral duty and thereby, an egalitarian, just and sustainable socio-economical order in the increasingly complex world we live in.